THE EFFECT OF MENSTRUAL EDUCATION ON READINESS TO FACE MENARCHE - Cahyanie, Choiru Nissatyas; Purwaningsih, heni; Sulastri, Sulastri (Jurnal Keperawatan, 2025)
Menarche is the first menstruation that occurs in early adolescence. Based on data from the Indonesian Ministry of Health, the incidence of menarche in Indonesia is around 12.4 years. However, most adolescent girls lack understanding of how to maintain hygiene during menstruation. This unpreparedness can lead to anxiety and health problems. One of the effective educational methods is to use role play techniques to improve the readiness of adolescent girls in facing menarche. This study aims to determine the effect of menstrual education on readiness to face menarche in adolescent girls. This study used a pre-experiment design with a one group pre-test post-test design. The sample consisted of 30 female students at SDN 02 Banjarharjo who were given education about menstruation using the role play method. Readiness to face menarche was measured before and after the education was conducted. Before education, most schoolgirls (53.3%) had an unprepared level of readiness. After being given education, all female students showed readiness (100%). The results of statistical analysis showed a p-value of 0.000, which indicated a significant difference between the level of readiness before and after menstrual education. Menstrual education using the role play method was proven effective in improving the readiness of adolescent girls to face menarche.